Collateral circulation via the circle of Willis in patients with carotid artery steno-occlusive disease: evaluation on 3-T 4D MRA using arterial spin labelling. Issue 9 (September 2015) - Iryo, Yasuhiko; Hirai, Toshinori; Nakamura, Masanobu; Inoue, Yasuteru; Watanabe, Masaki; Ando, Yukio; Azuma, Minako; Nishimura, Shinichiro; Shigematsu, Yoshinori; Kitajima, Mika; Yamashita, Yasuyuki
<x xml:space="preserve">Abstract</x> Aim To evaluate whether 3-T four-dimensional (4D) arterial spin-labelling (ASL) -based magnetic resonance angiography (MRA) is useful for assessing the collateral circulation via the circle of Willis in patients with carotid artery steno-occlusive disease. Materials and methods Institutional review board approval and prior written informed consent from all patients were obtained. The inclusion criteria were fulfilled by 13 patients with carotid artery steno-occlusive disease. All underwent 4D-ASL MRA at 3 T and digital subtraction angiography (DSA). The flow-sensitive alternating inversion recovery (FAIR) preparation scheme with look-locker sampling was used for spin labeling. At 300-ms intervals seven dynamic scans were obtained with a spatial resolution of 0.5×0.5×0.6 mm3. The collateral flow via the circle of Willis was read on 4D-ASL MRA and DSA images by two sets of two independent readers each. κ statistics were used to assess interobserver and intermodality agreement. Results On DSA, collateral flow via the anterior communicating artery (AcomA) was observed in six patients, via the posterior communicating artery (PcomA) in four patients, and via both the AcomA and PcomA in three patients. With respect to the qualitative evaluation of 4D-ASL MRA images, interobserver agreement was excellent for all items (κ=1). 4D-ASL MRA and DSA consensus readings agreed on the type of collateral flow pattern in 10 of the 13 patients (77%). Intermodality agreement was good (κ=0.606; 95% confidence interval (CI): 0.215–0.997). Conclusion 3 T 4D-ASL MRA may be a useful tool for the evaluation of the collateral circulation in patients with carotid artery steno-occlusive disease.